"Abba Father”, Jesus' Call to God in the Biblical Theological Perspective of Psalm 89:26 - Gulo, Arifman; Putrawan, Bobby Kurnia (Indonesian Journal of Religious, 2022)
We have been accepted as sons by the redemption of Jesus Christ, so that we may call God the Father. Therefore, let us live truly as children of God; live well and truly. For we want to touch his heart, call him by the name he loves. Call him Abba, Call Him Father. Of all his names, Abba The Father is Jesus ' call to God. We know that Jesus loved this name because it is the name that is most often used. When Jesus was on earth, he called God” Father " several times. In the prayer of victory on the cross, Jesus cried out with a loud voice; "Father, into your hands I commit my life” (Luke 23:46). God loves to be called Father. Jesus taught us to begin prayer with the words “Our Father”. Perfect love speaks of God's love. Since Jesus called God Abba, the love that can eliminate fear is the love of the Father. Agape love is perfect love, and that is the love of the father. He cares about us, he cares about us. Jesus cried Abba, O Father, so that we Christians who are given strength and salvation by-yes, can cry Abba, Father. We call him Abba, the Father because he is our Father, he cares for us, and He understands us. Perfect love exists only in the father and is able to eliminate all worries. If the Father loves Jesus as his son, the Father in heaven also loves us as his children as Christians who believe in the truth and the way of eternal salvation. For this reason, the author chose the title: "Abba Father", Jesus ‘call to God in the perspective of Biblical Theology from the book of Psalms 89:26, he will also cry out to me: 'My Father You Are God and my rock my salvation.’